Dress rehearsal for Russia's presidential election: Moscow tightens grip on regional governors and budgets - Fabian Burkhardt; Janis Kluge (Stiftung Wissenschaft und Politik (SWP), 2017)
Fifteen Russian regions and annexed Sevastopol elected new governors on 10 September 2017. The process reveals the Kremlin's response to rising socio-economic tensions in Russia's regions: changing their leaders. A string of older regional bosses rooted within their local elites have been forced to make way for a younger generation of political managers over whom Moscow holds greater sway. The regions' financial independence has been curtailed again too. For the Kremlin, this round of voting represented the final test before the presidential election scheduled for 18 March 2018 - and it passed off largely successfully. But the next presidential term will also see growing uncertain-ty over Vladimir Putin's successor in the Kremlin. These latest centralisation moves are designed to counter potential political risks ahead of time. But they weaken the incentives for governors to invest in the long-term development of their regions
Keywords: 320